ANALYSIS OF THE EFFECT OF CONCRETE QUALITY IN HOUSE CONSTRUCTION: A DECISION-MAKING MODEL BASED ON ENVIRONMENTALLY FRIENDLY CRITERIA - Burhanuddin; Badriana; Ezwarsyah; Syukriah; Bakhtiar; Fadliani (RADJA PUBLIKA, 2025)
This study analyzes the influence of concrete quality on house construction using a Decision Tree. Good concrete quality and proper maintenance are key factors for building sturdiness and longevity, especially in areas with varying environmental conditions. The study was conducted on 20 houses in three regions of Aceh, with samples selected purposively based on concrete quality documentation (K-225, K-300, K-350) and maintenance records. Data were collected through observation, project documentation, and interviews with contractors and builders. The analysis included descriptive, inferential (correlation and multiple regression), and the application of a Decision Tree to identify the concrete parameters most influential on building quality. The results indicate that concrete quality is the most critical factor, followed by maintenance quality and environmental conditions. Houses with high-quality concrete (K-300/K-350) and a minimum curing period of 14 days have optimal sturdiness, minimal cracking, and a longer service life. The Decision Tree produced a consistent pattern with 82.5% accuracy, while qualitative data reinforces these findings by emphasizing the importance of maintenance protocols and the quality of implementation in the field. This research provides practical implications in the form of minimum quality recommendations, standard maintenance protocols, and enhanced quality control. The results contribute to the development of a data-driven decision-making framework for selecting efficient, safe, and sustainable concrete specifications.